TINGKAT KEPEDULIAN MASYARAKAT DESA MERAGUN TERHADAP HUTAN LINDUNG GUNUNG NANING KECAMATAN NANGA TAMAN KABUPATEN SEKADAU - Jumhi, Maulidin; Roslinda, Emi; Setiyawati, Dina (Universitas Tanjungpura, 2015)
Gunung Naning Protection Forest (GNPF) were used by some Meragun Villagers as a source of livelihood. The aim of the research are to know the awareness level of Meragun villagers and the factors which have the relationship with the people awareness level toward the GNPF. The research was done in October 2014. The survey method was used in this research. The data analysis was used descriptively by using Chi-Kuadrat toward 87 respondents which was obtained purposively. The research result showed that 48 % of Meragun Villagers have the high level of awareness toward GNPF, 38 % was moderate, and 14 % was low. It was because of the existence of the awareness about the importance of GNPF role for their life. But some people still depend their life to the forest products and live in the area of GNPF. Age factor and knowledge factor have the relationship toward the awareness level with the moderate firmness level, meanwhile the peception factor has the relationship with the high firmness level. For the keeping, protecting, and conserving GNPF necessary make the regulation of forest product harvesting. It will to sustainable the forest product from GNPF. Keywords: Age, knowledge, perception, protection forest, the people awareness.